Simple and Effective Primary Assessment of Emergency Patients in a COVID-19 Outbreak Area: A Retrospective, Observational Study - Di G; Xia C; Yao S; Chen X; Wu Z; Hu L; Wang J (Dove Medical Press, 2020)
Gaohong Di,1 Chengkun Xia,1 Shanglong Yao,1 Xiangdong Chen,1 Zhilin Wu,1 Ling Hu,2 Jie Wang1 1Department of Anesthesiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2Department of Anesthesiology, Tianyou Hospital, Wuhan University of Science and Technology, Wuhan, Hubei, People’s Republic of ChinaCorrespondence: Jie Wang; Chengkun Xia Department of Anesthesiology of Wuhan Union Hospital, No. 1277 Jiefang Avenue, Hankou, Wuhan, Hubei, People’s Republic of ChinaTel/ Fax +86 27-85726834Email gatogiratorio@gmail.com; xiayulong_2001@163.comBackground: The rapid spread of COVID-19 has expanded into a pandemic, for which the main containment strategies to reduce transmission are social distancing and isolation of ill persons. Thousands of medical staff have been infected worldwide. Coronavirus testing kits have been in short supply, and early diagnostic reagents did not have high sensitivity. The aim of this study was to describe the characteristics of patients requiring emergency surgery in a COVID-19 outbreak area.Methods: We assessed medical data regarding all patients who underwent emergency surgery at the main campus of Wuhan Union Hospital from January 23, 2020, to February 15, 2020. We classified patients based on suspicion of COVID-19 infection (suspected vs not suspected) before they were admitted to the operating room. We used descriptive statistics to analyze the data. Outcomes included the incidence of confirmed COVID-19 infection and length of stay, which were followed until March 25, 2020.Results: Among the 88 emergency patients included in this study, the mean age was 37 years. Twenty-five patients presented with abnormalities observed on chest CT scans and 16 presented with fever. The median wait time for surgery was one day. The median preparation time and median time until short orientation memory concentration test (SOMCT) recovery from anesthesia were 44.0 min and 23.0 min, respectively. The median postoperative length of stay was five days. Compared with patients not suspected of COVID-19 infection, six patients were confirmed to be infected with COVID-19 in the suspected group. No health care workers were infected during this study period.Conclusion: Simple identification using temperature screening of patients, respiratory symptoms, and chest CT scans before being admitted for emergency surgery was rapid and effective. Shortened contact times might reduce the risk of infection. Additional investigations with larger samples and improved designs are needed to confirm these observations.Keywords: COVID-19, emergency, cross-infection